1976
DOI: 10.1128/iai.14.3.703-708.1976
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of mice treated with cyclophosphamide to lethal infection with Leptospira interrogans Serovar pomona

Abstract: Mice not normally susceptible to infection with Leptospira interrogans serovar pomona were rendered susceptible to lethal infections by treatment with a single dose of 300 mg of cyclophosphamide (Cy) per kg administered optimally from 4 days before to 1 day after infection. Cy-treated mice with either passively or actively acquired antibody were protected from death. Blood levels of leptospires in infected untreated and in Cy-treated mice remained similar until 2 days after infection, when untreated mice clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…Indeed, the three patients with estimated bacteremia to this level all died. Evidence for the concept of a critical threshold relating to lethality was previously obtained using a mouse model of leptospiral infection [10]. In one case (patient F), a decrease in the estimated number of circulating leptospires under the threshold of 10 4 leptospires ml −1 was observed, but this patient did not recover.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, the three patients with estimated bacteremia to this level all died. Evidence for the concept of a critical threshold relating to lethality was previously obtained using a mouse model of leptospiral infection [10]. In one case (patient F), a decrease in the estimated number of circulating leptospires under the threshold of 10 4 leptospires ml −1 was observed, but this patient did not recover.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, the three patients with estimated bacteremia to this level all died. Evidence for the concept of a critical threshold relating to lethality was previously obtained using a mouse model of leptospiral infection [10]. In one case (patient F), a decrease in the estimated number of circulating leptospires under the threshold of 10 4 leptospires ml 31 was observed, but this patient did not recover.…”
Section: Discussionmentioning
confidence: 91%
“…Immunoblotting sera from subjects 1-6 with har~o sonicate revealed that all produced 18M antibodies against the 15, 23 and 28 kDa components of hardjo LPS described previously [24]. Reaction with other hardjo antigens varied, although reactiun of IgM and/or IgG antibodies with the 34.5-35 kDa flagella doublet was observed with serum from most subjects.…”
Section: Discussionmentioning
confidence: 54%
“…It is also sisnificant that the vaocinees" sera protected hamsters from acute infection, similar to the protection reported for sera from naturally a~luired infections [20], in which anti-LPS ag-81urinating antibodies were involved. Although it was not possible to test anti-har~o antibodies for protective capacity it is reasonable to assume that they would also protect, in view of the correlation between agglutinatin& opsonizin8 and protective antibodies [13,24,25]. Our results thus confn-m that immunization of humans with protein-frec grown vaec~ne can induce the production of protective anti-LPS antibodies which appear to have a central role in immunity to infection, similar to the response following natural infection and to protection in animals [13,15,20].…”
Section: Discussionmentioning
confidence: 99%